Impact of working conditions on healthcare professionals’ intentions to change careers in Morocco: An empirical study - Moubtahij, Khalid; Bazine, Imad-dine; Mehdi, Sanae; ghaleb, Najoua El abbas El; Hachimi, Ikram El (Edelweiss Applied Science and Technology, 2025)
The loss of skilled workers in the healthcare sector is a global phenomenon that places increasing pressure on health systems, and Morocco is no exception. In a national context marked by the overhaul of the healthcare system, where human capital remains a central pillar, this issue takes on particular significance. This study aims to identify the key factors that drive nurses to consider a career change. To this end, we examined organizational, professional, and personal aspects through a quantitative survey conducted with this category of healthcare professionals. Among a sample of 157 nurses and healthcare technicians, 66% expressed a desire to change their current careers. This intention is either manifested by seeking opportunities in other sectors or by changing professions while remaining within the healthcare field. Participants made clear recommendations to encourage their retention in the profession, including salary increases, improvements in working conditions, enhanced organizational and social recognition, and a more suitable regulatory framework. The findings of this study provide policymakers with a detailed understanding of the factors fueling this phenomenon, thus enabling them to better shape public policies aimed at retaining healthcare professionals and ensuring the sustainability of the healthcare system in Morocco.